2019
DOI: 10.1002/hbe2.159
|View full text |Cite
|
Sign up to set email alerts
|

Boredom proneness and fear of missing out mediate relations between depression and anxiety with problematic smartphone use

Abstract: Depression and anxiety severity are found in numerous studies to correlate with increased levels of problematic smartphone use. Yet there are less available data on other psychopathology-related correlates of such use. Two potentially important variables related to depression and anxiety, and recently found related to problematic smartphone use severity, are boredom proneness and the fear of missing out (FOMO). Our aims were to (a) assess boredom proneness and FOMO in relation to problematic smartphone use sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 58 publications
10
73
1
2
Order By: Relevance
“…This finding is consistent with the I-PACE conceptualization of affective/cognitive responses (including responses to environmental stressors) as mechanisms explaining the psychopathology-excessive internet use relationship (Brand et al, 2019(Brand et al, , 2016. Prior work supports this conceptualization for affective/cognitive responses (e.g., Elhai et al, in pressa;Wegmann et al, 2017;Wolniewicz et al, 2020). However, mediation results were not supported for depression in the hypothesized model, nor for either psychopathology predictor in the revised SEM.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This finding is consistent with the I-PACE conceptualization of affective/cognitive responses (including responses to environmental stressors) as mechanisms explaining the psychopathology-excessive internet use relationship (Brand et al, 2019(Brand et al, , 2016. Prior work supports this conceptualization for affective/cognitive responses (e.g., Elhai et al, in pressa;Wegmann et al, 2017;Wolniewicz et al, 2020). However, mediation results were not supported for depression in the hypothesized model, nor for either psychopathology predictor in the revised SEM.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, COVID-19 anxiety (an affective response to environmental stressors) should demonstrate a meditational role between negative affectivity (general anxiety/depression) and PSU severity. Prior work has established numerous affective/cognitive response mediators between predisposing depression/anxiety and excessive internet/PSU severity (e.g., Elhai et al, in pressa;Wegmann et al, 2017;Wolniewicz et al, 2020).…”
Section: Hypothesesmentioning
confidence: 99%
“…Vishwanath () discovered that individuals who frequently utilized Facebook were significantly more likely to be habitual Facebook users. Other work has confirmed a relationship between frequency of any social media use and Facebook addiction (Hong et al, ; Koc & Gulyagci, ) and similar constructs like problematic smartphone use (Wolniewicz, Rozgonjuk, & Elhai, ). Descriptive studies also suggest a relationship between the intensity of use and social media addiction (Cabral, ; Olowu & Seri, ).…”
Section: Social Factorsmentioning
confidence: 76%
“…This has resulted in FoMO being consistently identified as a factor associated with problematic patterns of SNS engagement (Appel et al, 2019;Dhir et al, 2018;Oberst et al, 2017;Robson, 2018). A number of studies have also demonstrated correlations between FoMO and an array of psychological factors including psychological need satisfaction (Przybylski et al, 2013), depression (Oberst et al, 2017), anxiety (Wolniewicz et al, 2019), and general negative affect (Wolniewicz et al, 2018). FoMO has also been found to mediate the relationships between SNS use and a range of psychological and psychosocial factors including loneliness and depression (Reer et al, 2019), anxiety (Elhai et al, 2020), sensation seeking (Wang et al, 2019), and subjective well-being (Chai et al, 2019).…”
Section: Fomomentioning
confidence: 99%